(Jordanian Islamic banks Implemet the Cost-Based on Activites System (ABC - Beni Nasr, Abdelmalek Mohamed Amin (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to investigate Jordanian Islamic banks implementatiom of cost-based system activities. To achieve this goal, a questionnaire was designed according to the objectives and hypotheses of the study. The study population consisted of all employees of Islamic banks operating in the Hashemite Kingdom of Jordan. The study results indicated that the sample members agreed on terms that measure the application of the Jordanian Islamic banks to the system of costs based on the activities and the paragraph that states: The administrative structure helps in the implementation of the cost system based on anach E، ranked first، while the second ranked paragraph، which states: lead-based activities to reduce system costs indirect cost ratioThe result (1) validates the hypothesis that: The application of Islamic banks to the system of costs based on activities.The study recommended that the cost-based system should be applied to Islamic banks. The studies examined showed that the cost-based system reduces production costs due to the objectivity of indirect cost measurement measures and increases the ability of Islamic banks to benefit from their resources
Keywords: Islamic banks; system; activity-based costing system